Validation of the Italian version of the Pregnancy Physical Activity Questionnaire - Bianconi, Alessandro; Messina, Rossella; Ricci, Matteo; Leccese, Vincenza; Parma, Dila; Berini, Virginia; Rucci, Paola; Marini, Sofia; Dallolio, Laura; Masini, Alice (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. A growing body of evidence suggests that physical activity during pregnancy may have significant health benefits. Self-reported questionnaires may represent an important instrument for gathering information and quantifying the amount of physical activity that women engage during pregnancy. In this study we analyzed the reliability and validity of the Italian version of the Pregnancy Physical Activity Questionnaire.Methods. The reliability and construct validity of the Italian Version of the Pregnancy Physical Activity Questionnaire was analyzed in a sample of pregnant women. Intraclass correlation coefficients (ICCs) were calculated to investigate the test-retest reliability of the Italian Version of the Pregnancy Physical Activity Questionnaire scores at baseline and after 1 week. Intraclass correlation coefficients >0.70 were considered to denote an adequate reliability. Validity was assessed using Spearman’s rank order correlation coefficients between the Italian Version of the Pregnancy Physical Activity Questionnaire scores and the equivalent measures obtained by accelerometers. Coefficients (ρ) >0.50 were considered adequate for construct validity.Results. The test-retest analysis revealed an adequate reliability for sedentary (Intraclass correlation coefficient = 0.785), moderate (Intraclass correlation coefficient = 0.751), and vigorous physical activity (Intraclass correlation coefficient = 0.931), while lower reliability was found for total (Intraclass correlation coefficients = 0.689) and light physical activity (Intraclass correlation coefficients = 0.632). All Spearman’s rank correlation coefficients between the Italian Version of the Pregnancy Physical Activity Questionnaire and the accelerometers measures were